2007
DOI: 10.2214/ajr.07.2366
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic Assessment of Regional Adiposity

Abstract: It is highly plausible that sonography will be used in clinical practice for the routine assessment of regional adiposity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
74
0
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(82 citation statements)
references
References 53 publications
3
74
0
5
Order By: Relevance
“…Regional adiposity can be assessed by using anthropometric data and imaging techniques [11,12]. Among imaging techniques, Ultrasonographic assessment has attracted a considerable attention, as it combines safety, cost-effectiveness, accuracy [13] and with effectiveness, in the quantification of visceral fat, similar to that of computed tomography [14].…”
Section: Discussionmentioning
confidence: 99%
“…Regional adiposity can be assessed by using anthropometric data and imaging techniques [11,12]. Among imaging techniques, Ultrasonographic assessment has attracted a considerable attention, as it combines safety, cost-effectiveness, accuracy [13] and with effectiveness, in the quantification of visceral fat, similar to that of computed tomography [14].…”
Section: Discussionmentioning
confidence: 99%
“…Among these techniques, Ultrasonography has attracted considerable attention because it combines safety, cost-effectiveness, and accuracy [20]. Additionally, Pineau et al [21] have demonstrated similar effectiveness of both ultra-sonography and computed tomography in the quantification of visceral fat.…”
Section: Discussionmentioning
confidence: 99%
“…Visceral and subcutaneous adiposity measurements were performed according to Vlachos, Hatziioannou, Perelas, Perrea 31 , using a portable ultrasound device of the brand GE, model Logiq Book XP, for high-resolution ultrasonography, with 8 MHz linear transduction. The intra-observer coefficients for visceral and subcutaneous fat measures were 1.92% and .36%, respectively.…”
Section: Subcutaneous and Visceral Abdominal Ultrasonographymentioning
confidence: 99%